Evaluation of Corrosion Protection of Self-Healing Coatings Containing Tung and Copaiba Oil Microcapsules - Nicolas Augusto Paolini; Alexandre Gonçalves Cordeiro Neto; Alana Cristine Pellanda; Agne Roani de Carvalho Jorge; Bryan de Barros Soares; João Batista Floriano; Marcos Antonio Coelho Berton; Poornima Vijayan P; Sabu Thomas (International Journal of Polymer Science)
The objective of the current research is to evaluate and compare the corrosion protection efficiency of the microcapsules containing tung oil and copaiba oil using stereoscopic images, electrochemical tests, open circuit potential (OCP), and polarization curves (Tafel analysis). Carbon steel plates were painted with three different coating systems: (a) a coating system with an automotive primer which served as the control, (b) a coating system with microcapsules containing 3% tung oil, and (c) a coating system with microcapsules containing 3% copaiba oil. A crosscut was performed using a scalpel on the coating surfaces to promote the release of the oils, and after drying, electrochemical cells were assembled using electrolyte 3% NaCl. From OCP analyses, it was verified that the coating system containing tung oil loaded microcapsules obtained more positive final values than the control system and the coating system containing copaiba oil loaded microcapsules. The stereoscope images corroborate the OCP results, and the polarization curve analyses also indicated that the microcapsules containing tung oil offer better corrosion protection than the other systems studied.